Comparative Studies of Blood Mineral Profiles in Between Infertile and Normal Cyclic Buffaloes of Northwestern Himalayan Region - Kumar, Pravesh; Singh, Madhumeet; Sharma, Akshay; Singh, Geetanjali (The Indian Journal of Animal Reproduction, 2024)
Present study was undertaken in buffaloes (n=176) of different districts of Himachal Pradesh to study the effect of different minerals attributes on buffalo infertility. These profiles of different types of infertile (endometritis and anestrus) buffaloes was evaluated and compared with normal cyclic. Different estimated minerals calcium, phosphorous, magnesium, copper, zinc, sodium were significantly altered in infertile buffaloes in comparison to normal cyclic buffaloes.
Keywords: Anestrus; Endometritis; Buffaloes; Normal cyclic